Downside risk e médias móveis para otimização de carteiras investimentos e do processo de compra e venda de ativos financeiros - Rodrigues, Denise Maria (Universidade Federal de São Carlos, 2025)
This work proposes the optimization of investment portfolios through modeling with Quadratic Programming, using the Downside Risk model to minimize potential losses, which makes it more suitable for conservative profiles than traditional risk measures. In addition, moving average analysis is incorporated as a tool to assist in asset buy and sell decisions. The mathematical model was implemented in Python, considering practical allocation constraints and real data from the stock market. Three distinct portfolios were constructed and analyzed over different time windows, with performance compared to the Ibovespa index. The results show that the proposed methodology produced portfolios with superior performance in terms of risk-adjusted return. The research contributes to the practical application of Operations Research methods in Finance, reinforcing the role of mathematical optimization in decision-making under uncertainty.
Downside risk and moving averages for portfolio optimization and the buy-and-sell process of financial assets
Keywords: Downside risk; Médias móveis; Programação linear; Otimização de carteiras; Moving averages; Linear programming; Portfolio optimization; ENGENHARIAS::ENGENHARIA DE PRODUCAO::PESQUISA OPERACIONAL